Zirconium sulfate doped molecular sieve catalyst and preparation and application thereof

Through the sulfurization treatment of zirconium-doped molecular sieve, the problems of low efficiency and severe self-polymerization reaction of acrylic acid hydration method in the prior art were solved, and efficient catalysis and selectivity were improved, and the service life of the catalyst was extended.

CN119500243APending Publication Date: 2025-02-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411670954.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The catalysts used to prepare 3-hydroxypropionic acid by hydrating acrylic acid are inefficient, and there is a problem of severe acrylic self-polymerization reaction, and there is a lack of an efficient catalytic system.

Method used

By sulfation treatment of zirconium-doped molecular sieve, the acrylic dimerization reaction is inhibited by the pore size defined by the molecular sieve, and the introduction of solid superacids increases the acidity of the catalyst, thereby inhibiting the dimerization of acrylic acid and improving the selectivity of 3-hydroxypropionic acid.

Benefits of technology

The hydration reaction efficiency is improved, acrylic polymerization is inhibited, the selectivity of 3-hydroxypropionic acid is improved, and the service life of the catalyst is extended.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a zirconium sulfate doped molecular sieve catalyst for preparing 3-hydracrylic acid by hydrating acrylic acid. A preparation method of the catalyst comprises the following steps: (1) preparing a zirconium doped molecular sieve and (2) sulfating. The acrylic acid dimerization reaction is inhibited by using the pore size limited by the molecular sieve, and the solid superacid is introduced by doping zirconium and further sulfating treatment, so that the acidity of the catalyst is improved, the dimerization of acrylic acid is inhibited, the selectivity of 3-hydracrylic acid is improved, and the service life of the catalyst is prolonged. The preparation conditions of the catalyst are mild, and the process is stable and controllable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalytic method for preparing 3-hydroxypropionic acid by using an acrylic acid hydration method, and in particular to a catalytic hydration method of acrylic acid and water on a sulfated zirconium-doped molecular sieve. Background Art

[0002] 3-Hydroxypropionic acid is a highly promising plastic monomer and chemical intermediate with excellent biocompatibility, nonlinear optical activity and piezoelectricity. 3-Hydroxypropionic acid is an important monomer for the synthesis of biodegradable material poly(3-hydroxypropionic acid) (P3HP). P-3HP is the shortest-chain polyhydroxyalkanoate (PHAs) with good mechanical properties and excellent ductility. It has important applications in packaging (replacing traditional polymers such as PP and PE), biomedical materials, textile fibers, agriculture and other fields.

[0003] There are two methods for synthesizing 3-hydroxypropionic acid: biological method and chemical method. Currently, the biological method is reported more frequently. However, the biological method has a long fermentation process, slow progress in separation and purification process, and small production scale. Chemical methods include 3-propiolactone hydrolysis (JACS, 1950, 72, 3267), 3-hydroxypropionitrile acidification, 3-hydroxypropionaldehyde oxidation (DE4107987, DE19629371), vinyl acetate carbonylation (US2006 / 0128985), propylene alcohol oxidation (US9873653B2, ChemSusChem, 2009, 2, 57), 1,3-propylene glycol oxidation (DE4107987A), tetrahydrofuran oxidation (CN111423321A), 3-methoxypropionic acid methyl ester hydrolysis (CN116351457A), and acrylic acid hydration (JP2006131566A, CN102746141A, CN110981718B, CN113461512A). Among them, the acrylic acid hydration method has relatively mild reaction conditions and easy-to-control operation conditions. During the hydration reaction of acrylic acid, the main side reaction is the self-polymerization of acrylic acid under high temperature and strong acid conditions. Currently reported acrylic acid hydration catalysts generally have problems such as low efficiency and violent self-polymerization of acrylic acid, and lack of efficient catalytic system.

[0004] The present invention develops a new method for preparing a catalyst for preparing 3-hydroxypropionic acid by hydrating acrylic acid. The zirconium-doped molecular sieve is sulfated, the dimerization reaction of acrylic acid is inhibited by using the pore size limited by the molecular sieve, and a solid superacid is introduced to improve the acidity of the catalyst, which not only inhibits the dimerization of acrylic acid, but also improves the selectivity of 3-hydroxypropionic acid and prolongs the service life of the catalyst. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention provides a high-efficiency catalyst for preparing 3-hydroxypropionic acid by continuous hydration of acrylic acid, which can improve the hydration reaction efficiency, inhibit the polymerization of acrylic acid, and improve the selectivity of 3-hydroxypropionic acid.

[0006] The technical solution is:

[0007] The method for preparing a 3-hydroxypropionic acid catalyst by reacting acrylic acid and water comprises the following steps:

[0008] (1) Preparation of zirconium-doped molecular sieve: zirconium doping is performed by ion exchange method, wherein a zirconium source is dissolved in ethanol, an uncalcined molecular sieve containing a template is added, and the mixture is heated and stirred at a certain temperature for a certain period of time, and then filtered, dried, and calcined to obtain a zirconium-doped molecular sieve;

[0009] (2) Sulfate treatment: The zirconium-doped molecular sieve is added into a sulfuric acid solution at a solid-liquid ratio of 1 / 5 and immersed for a period of time, and then filtered, dried and calcined to obtain a sulfated zirconium-doped molecular sieve catalyst.

[0010] The key to the present invention is to sulfatize the zirconium-doped molecular sieve, utilize the pore size limited by the molecular sieve to inhibit the dimerization reaction of acrylic acid, introduce solid superacid to improve the acidity of the catalyst, which not only inhibits the formation of acrylic acid dimer but also improves the selectivity of 3-hydroxypropionic acid and prolongs the service life of the catalyst.

[0011] Preferably, in step (1), the molar ratio of the template to silicon is 0.3-0.6; the zirconium source is zirconium nitrate pentahydrate, and the concentration of the zirconium source in ethanol is 20 g / L; the molecular sieve is ZSM-5 molecular sieve (Si / Al is 23); the Zr / Si molar ratio is 0.05; the ion exchange temperature is 60-80°C; the ion exchange time is 18-24h; the suspension after ion exchange is filtered, dried at 120°C for 12h, and calcined at 550-600°C for 4-6h to obtain a zirconium-doped molecular sieve.

[0012] Preferably, in step (2), the concentration of the sulfuric acid impregnation solution is 0.5-2 mol / L; the solid-liquid ratio (solid mass g / liquid volume mL) is 1 / 5; the impregnation time is 4-6 h; the suspension after impregnation is filtered, dried at 120° C. for 12 h, and then calcined at a calcination temperature of 550-600° C. for 4-6 h; and after cooling to room temperature, the sulfated zirconium-doped molecular sieve is obtained.

[0013] A sulfated zirconium-doped molecular sieve catalyst for preparing 3-hydroxypropionic acid by hydrating acrylic acid is used in the reaction of preparing 3-hydroxypropionic acid by hydrating acrylic acid.

[0014] Preferably, a fixed bed reactor is used, the raw material is an aqueous solution of acrylic acid, the mass concentration is 25-50%; the inhibitor is p-methoxyphenol, the mass ratio of the inhibitor to acrylic acid is 0.05-0.2%; the reaction temperature is 120-180°C; the reaction pressure is 0.5-1.5MPa; based on the mass of the raw material, the mass space velocity is 0.75-2h -1 .

[0015] The invention treats zirconium-doped molecular sieves by sulfation, uses the pore structure of the molecular sieve with limited size to inhibit the self-polymerization of acrylic acid, introduces solid superacid by sulfation treatment, improves the selectivity of 3-hydroxypropionic acid, and prolongs the service life of the catalyst. The preparation conditions of the catalyst are mild, and the process is stable and controllable.

[0016] Beneficial technical effects

[0017] 1. The present invention performs sulfation treatment on the zirconium-doped molecular sieve, which not only utilizes the pore structure of the molecular sieve with a specific size, but also introduces a solid superacid to improve the acidity of the catalyst, which helps to inhibit the formation of acrylic acid dimerization intermediates, improve the selectivity of 3-hydroxypropionic acid, and extend the service life of the catalyst.

[0018] 2. The catalyst preparation process is simple, controllable and easy to operate, and has broad application prospects. DETAILED DESCRIPTION

[0019] In order to further explain the present invention in detail, several specific implementation cases are given below, but the present invention is not limited to these embodiments.

[0020] Example 1

[0021] (1) Preparation of zirconium-doped molecular sieve: 2.0 g zirconium nitrate pentahydrate and 6.8 g tetrapropylammonium hydroxide were dissolved in 100 mL anhydrous ethanol, 5 g commercially available (uncalcined and containing template, the same below) ZSM-5 molecular sieve (Si / Al is 23) was weighed and added to the above ethanol solution, stirred at 60° C. for 18 h, filtered, washed to neutrality, dried at 120° C. for 12 h, and the obtained solid was calcined in a muffle furnace at 550° C. for 4 h to obtain a zirconium-doped ZSM-5 molecular sieve, denoted as Zr-ZSM-5;

[0022] (2) Sulfate treatment: The Zr-ZSM-5 prepared in step (1) was added to a 1 mol / L sulfuric acid solution at a solid-liquid ratio of 1 / 5 (solid mass g / liquid volume mL), stirred at room temperature for 4 h, the obtained suspension was filtered and dried at 120°C for 12 h, and the obtained solid was calcined at 550°C for 4 h to obtain a sulfated zirconium-doped molecular sieve (SO4 2- / Zr-ZSM-5), denoted as catalyst 1, the XRD spectrum showed that the synthesized material had the characteristic diffraction peaks of ZSM-5, and the Zr content measured by ICP was 5.2%.

[0023] (3) Catalyst evaluation: The catalyst was evaluated in a fixed bed tubular reactor. The raw material was an aqueous solution of acrylic acid with a mass concentration of 50%. The mass concentration of the inhibitor hydroquinone in the reaction material was 0.1%. The reaction temperature was 180°C, the reaction pressure was 1.0 MPa, and the mass space velocity was 1.0 h -1 The composition and content of the product were analyzed by high performance liquid chromatography, and the conversion rate of acrylic acid and the selectivity of 3-hydroxypropionic acid were calculated.

[0024] Comparative Example 1

[0025] Comparative Example 1 is compared with Example 1. The process and conditions are the same as those of Example 1, except that step (1) is omitted, the solid added in step (2) is commercially available ZSM-5, and the rest is exactly the same as that of Example 1; the obtained catalyst is recorded as Catalyst 2. The catalyst evaluation conditions are the same as those of Example 1.

[0026] Comparative Example 2

[0027] Comparative Example 2 is compared with Example 1. The process and conditions are the same as Example 1, except that step (2) is omitted. The rest is exactly the same as Example 1. The catalyst obtained is recorded as Catalyst 3. The catalyst evaluation conditions are the same as Example 1.

[0028] Example 2: Different zirconium sources

[0029] Compared with Example 1, Example 2 has the same process and conditions as Example 1, except that the zirconium source in step (1) is tetrabutyl zirconate, and the amount used is 1.6 g, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 4. The catalyst evaluation conditions are the same as those in Example 1.

[0030] Example 3: Different zirconium sources

[0031] Compared with Example 1, Example 3 has the same process and conditions as Example 1, except that the zirconium source in step (1) is zirconium oxychloride octahydrate, and the amount used is 1.3 g, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 5. The catalyst evaluation conditions are the same as Example 1.

[0032] Example 4: Different Zr / Si molar ratios

[0033] Compared with Example 1, Example 4 has the same process and conditions as Example 1, except that in step (1), the amount of zirconium nitrate pentahydrate used is 0.36 g, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 6. The catalyst evaluation conditions are the same as Example 1.

[0034] Example 5: Different Zr / Si molar ratios

[0035] Compared with Example 1, Example 5 has the same process and conditions as Example 1, except that in step (1), the amount of zirconium nitrate pentahydrate used is 3.58 g, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 7. The catalyst evaluation conditions are the same as Example 1.

[0036] Example 6: Different ion exchange temperatures and times

[0037] The difference between Example 6 and Example 1 is that in step (1), the ion exchange temperature is 40° C. and the ion exchange time is 24 h. The rest is exactly the same as Example 1. The obtained catalyst is recorded as Catalyst 8. The catalyst evaluation conditions are the same as those in Example 1.

[0038] Example 7: Different ion exchange temperatures and times

[0039] The difference between Example 7 and Example 1 is that in step (1), the ion exchange temperature is 80° C. and the ion exchange time is 12 h. The rest is exactly the same as Example 1. The obtained catalyst is recorded as Catalyst 9. The catalyst evaluation conditions are the same as those in Example 1.

[0040] Example 8: Different ion exchange temperatures and times

[0041] The difference between Example 8 and Example 1 is that in step (1), the ion exchange temperature is 80° C., and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 10. The catalyst evaluation conditions are the same as those in Example 1.

[0042] Example 9: Different ion exchange temperatures and times

[0043] The difference between Example 9 and Example 1 is that in step (1), the ion exchange time is 24 hours, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 11. The catalyst evaluation conditions are the same as those in Example 1.

[0044] Example 10: Different concentrations of sulfuric acid immersion solution and treatment time

[0045] Compared with Example 1, Example 10 is different in that, in step (2), the concentration of the sulfuric acid solution is 0.5 mol / L, the treatment time is 8 h, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 12. The catalyst evaluation conditions are the same as those in Example 1.

[0046] Example 11: Different concentrations of sulfuric acid immersion solution and treatment time

[0047] Compared with Example 1, Example 11 is different in that, in step (2), the sulfuric acid treatment time is 2 hours, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 13. The catalyst evaluation conditions are the same as those in Example 1.

[0048] Example 12: Different concentrations of sulfuric acid immersion solution and treatment time

[0049] The difference between Example 12 and Example 1 is that in step (2), the concentration of the sulfuric acid solution is 2 mol / L, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 14. The catalyst evaluation conditions are the same as those in Example 1.

[0050] Example 13: Calcination temperature and time are different

[0051] The difference between Example 13 and Example 1 is that in step (2), the calcination temperature is 450° C. and the calcination time is 8 h. The rest is exactly the same as Example 1. The obtained catalyst is recorded as Catalyst 15. The catalyst evaluation conditions are the same as those in Example 1.

[0052] Example 14: Calcination temperature and time are different

[0053] The difference between Example 14 and Example 1 is that in step (2), the calcination time is 2 h, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 16. The catalyst evaluation conditions are the same as those in Example 1.

[0054] Example 15: Calcination temperature and time are different

[0055] The difference between Example 15 and Example 1 is that in step (2), the calcination temperature is 650° C., and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 17. The catalyst evaluation conditions are the same as those in Example 1.

[0056] Example 16: Different types of molecular sieves

[0057] Compared with Example 1, Example 16 is different in that the molecular sieve in step (1) is a commercially available Y molecular sieve, the Si / Al ratio is 15, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 18. The catalyst evaluation conditions are the same as those in Example 1.

[0058] Example 17: Different types of molecular sieves

[0059] Compared with Example 1, Example 17 is different in that the molecular sieve in step (1) is a commercially available β molecular sieve, the Si / Al ratio is 12.5, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 19. The catalyst evaluation conditions are the same as those in Example 1.

[0060] Example 18: Different types of molecular sieves

[0061] Compared with Example 1, Example 18 is different in that the molecular sieve in step (1) is a commercially available MCM-41 molecular sieve, and the rest is exactly the same as Example 1; the obtained catalyst is recorded as Catalyst 20. The catalyst evaluation conditions are the same as those in Example 1.

[0062] The following table lists the reaction evaluation results of the catalyst prepared by the method of the present invention:

[0063] Example Acrylic acid conversion rate / % 3-Hydroxypropionic acid selectivity / % Dimer selectivity / % Example 1 87.1 90.2 1.8 Comparative Example 1 51.6 67.8 24.8 Comparative Example 2 68.5 82.8 7.5 Example 2 82.5 86.7 3.6 Example 3 83.6 86.9 4.5 Example 4 80.3 83.6 8.1 Example 5 85.1 86.9 5.2 Example 6 83.8 85.6 4.5 Example 7 84.1 85.3 4.9 Example 8 83.9 85.9 4.6 Example 9 84.5 87.8 2.5 Example 10 80.8 83.3 7.8 Embodiment 11 82.6 84.1 6.5 Example 12 84.6 85.8 4.9 Example 13 81.0 83.1 8.8 Embodiment 14 84.5 87.6 3.5 Embodiment 15 83.6 87.9 3.3 Example 16 84.6 82.1 8.9 Embodiment 17 84.5 82.8 8.4 Embodiment 18 80.5 81.6 9.0

[0064] From Example 1 and Comparative Examples 1 and 2, it can be seen that zirconium doping and sulfation treatment are beneficial to improving the conversion rate of acrylic acid and the selectivity of 3-hydroxypropionic acid, and inhibiting the formation of acrylic acid dimerization; from Examples 2-15, it can be seen that the catalyst prepared under Condition 1 has the best performance; from Examples 1 and 16-18, it can be seen that for Y, β and MCM-41 molecular sieves, zirconium doping followed by sulfation treatment helps to improve the reaction activity and inhibit acrylic acid polymerization, but ZSM-5 has the best effect.

Claims

1. A method for preparing a sulfated zirconium-doped molecular sieve catalyst, The preparation of the catalyst comprises the following steps: (1) Preparation of zirconium-doped molecular sieve: using an ion exchange method, a zirconium source and a template are dissolved in ethanol, a commercially available (uncalcined template-containing) molecular sieve is added, heated and stirred, solid-liquid separation is performed, the solid is dried, and calcined to obtain a zirconium-doped molecular sieve; (2) Sulfate treatment: The zirconium-doped molecular sieve is added to a sulfuric acid solution for immersion treatment, followed by solid-liquid separation, solid drying, and calcination to obtain a sulfated zirconium-doped molecular sieve catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), the template is one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and hexadecyltrimethylammonium bromide; and the molar ratio of the template to silicon is 0.1-1.0, preferably 0.3-0.

6.

3. The preparation method according to claim 1, characterized in that: In step (1), the zirconium source is one or more of zirconium nitrate pentahydrate, tetrabutyl zirconate and zirconium oxychloride octahydrate, preferably zirconium nitrate pentahydrate; the concentration of the zirconium source in ethanol is 5-100 g / L, preferably 10-50 g / L, more preferably 20 g / L; The molecular sieve is one or more of ZSM-5, Y, β and MCM-41, preferably ZSM-5 molecular sieve; The Zr / Si molar ratio is 0.01-0.2, preferably 0.01-0.1, more preferably 0.03-0.08; The ion exchange temperature is 40-80°C, preferably 60-80°C; The ion exchange time is 12-24h, preferably 18-24h; The suspension after ion exchange is filtered, dried at 80-160° C. for 4-24 h, and calcined at 450-650° C. (preferably 550-600° C.) for 2-8 h (preferably 4-6 h) to obtain a zirconium-doped molecular sieve.

4. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the sulfuric acid immersion solution is 0.1-5 mol / L, preferably 0.5-2 mol / L; The solid-liquid ratio (solid mass g / liquid volume mL) is 1 / 2-1 / 20, preferably 1 / 5; The immersion time is 2-8 hours, preferably 4-6 hours; The impregnated suspension is filtered, dried at 80-160°C for 4-24h and then calcined at a temperature of 450-650°C, preferably 550-600°C, for 2-8h, preferably 4-6h; after calcination, the temperature is cooled to room temperature to obtain a sulfated zirconium-doped molecular sieve.

5. A catalyst prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the catalyst according to claim 5 in catalyzing the hydration of acrylic acid to prepare 3-hydroxypropionic acid.

7. The method according to claim 6, characterized in that: A fixed bed reactor is used, the raw material is an aqueous solution of acrylic acid, the mass concentration is 15-75%, preferably 25-50%; the inhibitor is one or more of hydroquinone, p-methoxyphenol and phenothiazine, the mass ratio of the inhibitor to acrylic acid is 0.01-1%, preferably 0.05-0.2%; the reaction temperature is 100-200°C, preferably 120-180°C; the reaction pressure is 0.1-2MPa, preferably 0.5-1.5MPa; based on the mass of the raw material, the mass space velocity is 0.5-5h -1 , preferably 0.75-2h -1 .

Citation Information

Patent Citations

  • Method for synthesizing beta-hydroxy propionic acid

    CN102746141A

  • A method for the continuous hydration of acrylic acid to prepare 3-hydroxypropionic acid

    CN110981718B

  • Environment-friendly and efficient synthesis method of 3-hydracrylic acid

    CN111423321A

  • Preparation method of 3-hydracrylic acid

    CN113461512A

  • Catalyst, preparation method thereof and method for preparing 3-hydracrylic acid by catalyzing hydrolysis of methyl 3-methoxypropionate by using catalyst

    CN116351457A